Twisted tressess: a rare case series of familial woolly hair - Jabeen, Masarat; Kaur, Gurkim; Sharma, Ennakshee; Dogra, Devraj (International Journal of Contemporary Pediatrics, 2022)
Woolly hair is an uncommon congenital anomaly of the scalp hair presenting with strongly coiled hair involving a localized area of the scalp or covering the entire side and occurring in non-black people. Among the syndromes presenting with woolly hair, the most known are the Naxos syndrome, the Carvajal-Huerta syndrome, the woolly hair/hypotrichosis, the ectodermal dysplasia-skin fragility and the tricho-hepato-enteric syndrome. Case characteristics: herein, we report a case of autosomal recessive familial woolly hair of an Asian female child and member of a family, her younger brother affected by a localised woolly hair, not associated to complications. Children with woolly hair must be examined completely and monitored regularly to rule out cardiofaciocutaneous and Noonan syndrome.